A Saúde Bucal nos Municípios da DIR V – Osasco: a experiência do Comitê de Saúde Bucal da região - Martino, Fausto Souza; Martino, Luiz Vicente Souza; Barros, Rebeca Silva de; Botazzo, Carlos (Boletim do Instituto de Saúde - BIS, 2007)
.